DAYA DUKUNG LINGKUNGAN DALAM PERKEMBANGAN OBJEK WISATA PANTAI GANDORIAH DI KOTA PARIAMAN - Khailinda, Ranti - (Pendidikan Geografi, 2014)
This research aims to describe and analyze the carrying capacity of the environment in the development of the Gandoriah beach attractions in Pariaman city, seen from : 1) Infrastructure. 2) Natural Beauty. 3). Community Participation in the Management. The type of research in this study is the analysis of qualitative research sites attraction of Gandoriah beach in Pariaman city. The informants of this study numbered 17 include Head, surrounding community and visitors by using the techniques of documentations, observations, and interviews. Informants were taken by using purposive analysis of the data consists of data reduction, data presentation and conclusion. The results showed tha : the carrying capacity of the environment in the development of the Gandoriah beach attractions in the city of Pariaman are 1) Infrastructure of the Gandoriah beach Attractions still less marked by the lack of playground, the plan of built a bridge from island to island while the infrastructure is good enough to help the community and visitors. 2) The natural beauty characterized by a very nice arrangement of the gardens, making visitors more interested to this attraction. 3) Public participation in the development of Gandoriah beach only on cleanness in the environment, but in terms of keeping the infrastructure is less society